Placental Site Trophoblastic Tumor: A Case Report and Review of the Literature - Bouquet de la Jolinière, Jean; Khomsi, F.; Fadhlaoui, Anis; Ben Ali, Nordine; Dubuisson, Jean-Bernard; Feki, Anis (Frontiers in Surgery, 2014)
Trophoblastic tumors of placental site (PSTT) are rare. They represent a rare form of gestational trophoblastic disease. (GTD). They occur mainly in women who have a history of miscarriage, termination of pregnancy, or even a normal or pathological ongoing pregnancy. The clinical course is unpredictable. This malignancy has different characteristics from other gestational trophoblastic tumors. Following a clinical case that we encountered and treated, we conducted a literary research and review, focusing primarily on prognostic factors and treatment.